PENGARUH PENAMBAHAN DAUN GEDI (Abelmoschus manihot L.) TERHADAP KUALITAS FISIK DAN SENSORIS MI BASAH DARI SAGU BARUK (Arenga microcarpha Becc) - Suryani, Mulalinda W; Nurali, Erny J N; Oessoe, Yoachim Y E (Jurnal Teknologi Pertanian (Agricultural Technology Journal), 2021)
Sago ‘baruk’ (Arenga microcarpha) noodle is a kind of starch noodle, which in its processing relies on gelatinization and retrogradation processes for tissue formation. Gedi leaves (Abelmoschus manihot L.) contain protein in the mucilage and fiber. This study aims to analyze the physical and sensory qualities of the wet noodles produced and to determine the appropriate addition of gedi leaves in the processing of Sagu-Gedi wet noodles. This study used a completely randomized design with 5 treatments A (10% addition of gedi green leaf extract), B (15% addition of gedi green leaf extract), C (20% addition of gedi green leaf extract) D (25% addition of green gedi leaf extract) . The results showed that the addition of 25% gedi leaf extract in the manufacture of Sagu-Gedi wet noodles had the highest elasticity value of 3.80%, the addition of 20% of green Gedi leaf extract had the highest value of 6.54% and wet Sagu-Gedi noodles with the addition of 25 % green gedi leaf extract is the most preferred product by panelists in terms of color, aroma, texture and taste.